Features Of The Grammatical Structure And Making Of Anthroponyms - Kilichev Bayramali Ergashevich; Kozieva Iqbol Kamiljonovna (Peerian Journals Publishing, 2025)
The grammatical structure and features of making anthroponyms are widely revealed in Makola. On this basis, it can be further noted that the anthroponym is a lexical wealth of the Uzbek language, which is spoken in the Haki of the structure of the language, subordination to the laws of making. Also spoken of are the structural molds of anthroponyms, the appellative nature of anthroponyms, their distinctive features. Alternatively, simple structured anthroponyms, the suitability and essence of the structure of the lexeme on which they are based, are emphasized in the Haki of the correspondence of Indigenous names
Keywords: Anthroponymy; onomastics; anthroponymics